Glomerular Diseases: Systemic Lupus Erythematosus is Most Common Finding: A Cross-Sectional Study - Fadhil Handhal Khleif 1, Haider Jebur Kehiosh 2, Salman Azeez Aljubori3, Sabah Nemah Alfatlawi 4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The objective of this study was to assess the connection amongst’s immunological and histopathological findings of renal biopsy acquired from patients with glomerular diseases. This cross sectional study was done in Al-Kafil private hospital and included 110 patients who were diagnosed by nephrologist as having glomerulonephritis as per clinical introduction, physical examination and laboratory findings of biopsy. The age scope of patients enlisted in the present investigation was between 2.8 to 72 years. The study included 67 male patients (60.9%) and 43 female patients (39.1%). The examination began at January 2016 and reached out through January 2017. At the point when clinical introduction and the entire workup of examination were at long last joined, with exceptional accentuation on histopathology and immunofluorescent tiny examination, the accompanying classification was gotten. Cases with glomerular association optional to foundational lupus erythematosis represented 27 out of 110 (24.5%). Consequently lupus nephritis is the most incessant reason for glomerulonephritis obsereved in the present examination. As indicated by the International Society of Nephrology (ISN)/Renal Pathology Society (RPS) grouping of lupus nephritis, the most incessant compose was ISN/RPS class IV (A/C) represented 14 case (12.7%), trailed by ISN/RPS class III ( A/C) (8 case, 7.3%)